Understanding rhetoric : a graphic guide to writing (Boston : Bedford/St. Martin's, 2014)
This comics-style collaboration between rhetoricians Elizabeth Losh and Jonathan Alexander and illustrator team Big Time Attic presents the content of the composition course in a form designed to draw students inches Understanding Rhetoric: A Graphic Guide to Writing covers what first-year college writers need to know - the writing process, critical analysis, argument, research, revision, and presentation - in a visual format that brings rhetorical concepts to life through examples ranging from Aristotle to YouTube.
Introduction : Spaces for writing Discovering contexts for writing Going boldly through writing processes Exploring visual literacy reframe : why rhetoric? why a comic book? --Issue 1 : Why rhetoric? Piecing together a definition of rhetoric Reanimating ancient views of rhetoric Setting rhetorical concepts loose on the world reframe : what does Aristotle have to do with me? --Issue 2 : Strategic reading Investigating texts and analyzing meaning Putting the pieces together with synthesis Using reading strategies Imagining ideal readers reframe how do I read this? --Issue 3 : Writing identities Leaping into identities in writing Trying out choices for different audiences Revealing the performer within the text reframe what's my identity? --Issue 4 : Argument beyond pro and con Spotlighting strategies for argument Setting the scene for arguable assertions Zooming in on claims and evidence Focusing on effective organization reframe the office hour! --Issue 5 : Research : more than detective work Keeping the story straight Tracking down sources Deciding which sources to trust Making sources talk : summary, paraphrase, quotation Coming clean with citation reframe get a clue! --Issue 6 : Rethinking revision Looking beyond the red ink Reviewing rhetorically Seeing through others' eyes Revising radically reframe am I missing something? --Issue 7 : Going public Launching into the future of genres Navigating among media Entering the final frontier with publication reframe how does this look?
Includes index.
Keywords: English language -- Rhetoric -- Comic books, strips, etc; Rhetoric -- Comic books, strips, etc